Thermal characterization of an alkaline electrolysis cell for hydrogen production at atmospheric pressure. (15th September 2020) - Barco-Burgos, J.; Eicker, U.; Saldaña-Robles, N.; Saldaña-Robles, A.L.; Alcántar-Camarena, V.
Highlights: Design of alkaline electrolysis cell for hydrogen generation at atmospheric pressure. Study of distribution of temperature on the electrode surfaces. Electrolyzer performance and average hydrogen production rate are calculated. Abstract: The main contribution of the present work consists of the design and thermal characterization of an alkaline electrolysis cell for hydrogen generation at atmospheric pressure. The electrolytic cell was manufactured from acrylic, using 316 L stainless steel electrodes and considering a membrane separation for gases. The effect of current conditions, the distance between electrodes on the production efficiency of hydrogen and the distribution and variation of temperatures on the surface of the electrodes in operation were evaluated. Maximum hydrogen generation was achieved with a separation between electrodes (anode and cathode) of 3 mm and a current of 30 A at 12 V. Furthermore, the thermoelectric effects on the electrodes were analyzed, and the presence of areas of higher activity was discussed for oxidation and reduction reactions.